Prediction of the turbulent boundary layer separation - Chou, Fang-Kuo, author; Sandborn, Virgil A., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1973)
A method for the prediction of the location of turbulent boundary layer separation is developed. The method is based on the inner and outer velocity distributions technique developed by Stratford, together with a separation criterion, which applies directly to the separation position. For the inner region, the model employs the empirical one-parameter boundary layer separation profiles proposed by Sandborn and Kline. For the outer region, the equivalent velocity distribution for the flow on a flat plate has been used. The resulting formula for predicting the separation position is a simple non-linear algebraic equation. The method is tested by comparing with several well-documented separation measurements. The results show a good agreement in the prediction of the position of turbulent separation. The calculated pressure rise to separation is also in good agreement with experimental results. An experimental study for a turbulent boundary layer up to and through the separation region has been made to further demonstrate the present method. The measurements were taken along the test wall of a two dimensional diffuser. Mean quantities, turbulent intensities, and the wall shear stresses were measured. The velocity profile integral parameters were evaluated from the measured data. The results are also compared with the separation model suggested by Sandborn and Kline. At the start of the separation region, the velocity profile correlation falls approximately on the unrelaxed separation correlation curve given by Sandborn and Kline. The velocity profiles in the separation region are well represented by the two-parameter separation profiles suggested by Sandborn.
CER73-74-FKC-VAS3.
July 1973.
Prepared under Office of Naval Research, project no. NR 062-414/6-6-68 (Code 438).
Keywords: Aerodynamics; Boundary layer